Biodiversity of the white coral reefs in the Ionian Sea (Central Mediterranean) - TURSI, Angelo Raffaele; MASTROTOTARO, FRANCESCO; MATARRESE, Alfonso; MAIORANO, Porzia; D'ONGHIA, Gianfranco (2004)
Three surveys were carried out off Cape Santa Maria di Leuca (Southern Italy). Samples were taken using an ‘ingegno’, trawl net and traps at 630–1100m depth. The white coral biocoenosis in this area of the Ionian Sea consists of living corals mainly represented by the framework builders Lophelia pertusa and Madrepora oculata. The solitary corals Desmophyllum cristagalli and Stenocyathus vermiformis were also obtained alive. The polychaete Eunice norvegica is another characteristic species. A list of 58 species were compiled, indicating the Atlantic character of this biocoenosis and confirming Mediterranean biodiversity to be lower than that of ocean.